2015
DOI: 10.4103/2231-0746.161059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of isoamyl 2-cyanoacrylate tissue adhesive in management of pediatric lacerations: An alternative to suturing

Abstract: Aims:A study was conducted to evaluate the benefits of cyanoacrylate tissue adhesive as an alternative to suturing in management of pediatric lacerations.Materials and Methods:A total of 7 patients were evaluated and followed for 3-month. The wound was evaluated on 1st, 3rd, and 7th postoperative day for swelling, infection, gaping and pain and at 1st and 3rd postoperative month for scar evaluation. The evaluation was based on different superficial facial wound repairs (i.e., low tension) with an average lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
1
13
0
2
Order By: Relevance
“…CA converts into an inert polymer on coming in contact with moisture, solidifies within 5–10 s and fixes in a minute . It is bacteriostatic and extremely adhesive to biological tissue which makes it beneficial to occlude hydrosalpinx prior to IVF …”
Section: Discussionmentioning
confidence: 99%
“…CA converts into an inert polymer on coming in contact with moisture, solidifies within 5–10 s and fixes in a minute . It is bacteriostatic and extremely adhesive to biological tissue which makes it beneficial to occlude hydrosalpinx prior to IVF …”
Section: Discussionmentioning
confidence: 99%
“…Patients who satisfied the following criteria were included: facial lacerations were closed by emergency physicians, referral to plastic surgeons responsible for facial trauma in our ED was not requested at the ED, and wound review was performed by board‐certified plastic surgeons during a follow‐up visit and medical chart for wound review was available. Patients whose wounds had not been reviewed within 3 days after wound closure were excluded, since the initial wound review by a specialist within 3 days was recommended in our hospital policy and wound dehiscence is usually diagnosed in the first week . Also excluded were patients with facial injuries who visited our ED more than once during the study period.…”
Section: Methodsmentioning
confidence: 99%
“…However, a 2015 survey found that pediatric patients reported significant dissatisfaction after facial wound closure by an emergency physician, which concerns the quality assurance of facial laceration repair by nonspecialists. Another prospective study at a pediatric ED in the United States showed that 8.2% of simple and small superficial facial lacerations repaired by nonspecialists had complications at short‐term follow‐up, which is a higher incidence than for facial trauma specialists (1.4%–5.2%) reported in previous studies …”
mentioning
confidence: 86%
“…En el cierre de heridas cutáneas faciales con un mínimo de tensión, si bien se describen casos de dehiscencia y cicatriz hipertrófica, las diferencias no serían significativas, con buenos resultados estéticos (19) . Deorukhkar el at (30) , evaluaron en 2015 la utilidad de los ACA en el cierre de heridas faciales superficiales con baja tensión en niños. En ninguno de los casos se observó infección de la herida en el 1º, 3º y 7º día del postoperatorio y sólo uno de los casos mostró dehiscencia de la herida en el 3° día del postoperatorio.…”
Section: Utilidad En Cierre De Heridas En Piel Y Mucosaunclassified
“…En ninguno de los casos se observó infección de la herida en el 1º, 3º y 7º día del postoperatorio y sólo uno de los casos mostró dehiscencia de la herida en el 3° día del postoperatorio. En general, no fue necesario inyectar anestésico local y la evaluación estética fue satisfactoria (30) . En la mucosa oral, la calidad de los tejidos, la saliva, la vascularización y las funciones relacionadas con el habla, la masticación y la deglución (27) , influyen en que las suturas se puedan comportar de manera diferente.…”
Section: Utilidad En Cierre De Heridas En Piel Y Mucosaunclassified